El Cid - Heston, Charlton; Loren, Sophia, 1934-; Samuel Bronston Productions; United Home Video ([s.l.] United Home Video, 1987)
Epic drama of Spain's eleventh-century hero who conquered the Moors.
Videocassette of the 1961 motion picture released by Samuel Bronston Productions.
VHS format.
Writers, Fredric M. Frank, Philip Yordan ; music, Miklos Rozsa ; photography, Robert Krasker ; producer, Samuel Bronston ; director, Anthony Mann.
Charlton Heston, Sophia Loren, Raf Vallone, Genevieve Page, John Fraser, Gary Raymond, Hurd Hatfield, Massimo Serato.
Keywords: Feature films